Developing a Waqf Sociopreneurship Model for Strengthening Family Resilience in Roumah Waqf Surabaya - Sumarkan Sumarkan; Basar Dikuraisyin (Journal of Islamic Social Finance Management, 2026)
Abstract This study develops a family-centered waqf sociopreneurship model by examining how productive waqf is transformed into a sociopreneurship ecosystem for family stability and resilience. The family economy is the micro-institution most impacted by modern economic developments. Using a qualitative case study at the Surabaya Waqf House, data was collected through in-depth interviews, observation, and document analysis. The findings indicate that the family-centered waqf sociopreneurship model positions the family as a central mediating institution connecting waqf assets, sociopreneurship, family resilience, and sustainable social welfare. The family waqf management pattern is symbiotic, where the waqf donor donates his family's assets, but they receive the results of management as beneficiaries of the waqf. This pattern is called transformation.